(untitled) (Agro Productividad, 2025)
Objective: To describe and analyze the main practices and challenges associated with the Milpa Intercropped in Fruit Trees (MIAF) system in response to the climate variability due to climate change (CC) in the MIAF Module of San Andrés Tuxtla, Veracruz. Methodology: A climatological analysis of the study area was conducted, along with a review of adaptation practices to climate change and the conceptual framework of the milpa system, climate change, and adaptation, using the Scopus platform. Review metrics and a bibliometric analysis were generated using VOSviewer. Results: In the 1970s, maximum temperatures were lower as compared to the 1950s and 1980s. Four adaptation strategies implemented in the MIAF system in response to climate change were identified, focused on water management, biodiversity, agronomic practices, and the functionality of those strategies. A total of 12 relevant documents published between 2018 and 2022 were found, comprising 75% scientific articles, 16.7% essays, and 8.3% book chapters. The publications comes from Mexico, the United States, the United Kingdom, and Philippines. The predominant thematic areas were environmental sciences (30.4%), social sciences (26.1%), and agriculture (13.0%). Conclusions: The study reveals a limited amount of literature on the subject. Furthermore, the MIAF system faces critical challenges, including the need to adapt traditional agricultural practices to increasingly extreme climatic conditions, the transfer of knowledge and adaptive technologies to rural communities, and the potential decline in crop yields due to fluctuations in temperature and precipitation.